(untitled) (City: History, Culture, Society, 2023)
Sociological science is weakly or not at all related with museums and museum space. Typically, the museum’s focus is limited to historical science. Other techniques and optics are categorized as either related or thematically centered on specific elements or concerns. Sociology actually finds itself in an interdisciplinary context and in museum-commissioned concrete-empirical research scenarios. This essay examines the sociological perspective on museums as socially institutionalized environments (science, politics, economics, culture, leisure, everyday life, identity and socialization). We occupy the 176 specialized niche of “sociology museum” or “museum sociology”. Our focus is on the sociological perspective of the social processes that surround the emergence, operation, and potential of museums and museum practices. In two ways, museum space is viewed as a component of social ecumenism: a) through sociology’s position in the knowledge and study of museum practices, and b) through the role analysis of museums in their own understanding of self-formation as elements of the social system (in functionalist meaning). The socio-spatial setting of museums is examined as a component of a settlement unit (city). The cultural, social, economic, and political aspects of a museum’s operation are strongly influenced by the local migratory dynamics. Therefore, museums in modern cities must take these processes into account. Local museums must construct scenarios of interaction between the local population and visitors in order to foster a social climate of understanding and loyalty, to implement adaptive measures to include tourists in the local context, and to organize events to round out the diversity of urban cultures within the context of the local community and its history. Commercialization, participation, and localization are some of the consequences and methods of museum operation that are observed. An element of the essay is the empirical component of the museum’s sociological research experience, which displays the case of sociology’s applied capabilities and practical tools in the establishment and operation of a specific museum.